PENGARUH IMPLEMENTASI MODEL PEMBELAJARAN OUTDOOR LEARNING TERHADAP MOTORIK DASAR DALAM PENDIDIKAN JASMANI SISWA KELAS 1 SDN 106158 PEMATANG JOHAR - Hosianna Kristiani Anggelina Simatupang (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low level of fundamental motor skills among first-grade students in Physical Education, Sports, and Health (PJOK) learning, indicating the need for an instructional model capable of improving students' basic movement skills more effectively. The purpose of this study was to determine the effect of implementing the Outdoor Learning model on the fundamental motor skills of first-grade students at UPT SPF SD Negeri 106158 Pematang Johar in the 2025/2026 academic year. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The research sample consisted of 50 students, including 25 students in the experimental class and 25 students in the control class. Data were collected using an observation sheet measuring fundamental motor skills that had met the requirements of content validity, empirical validity, and reliability. Data were analyzed using SPSS through normality tests, homogeneity tests, and the Independent Sample t-test. The findings revealed that the mean posttest score of the experimental class was 88.64, which was higher than the control class mean score of 55.60. The hypothesis testing yielded a significance value (Sig. 2-tailed) of < 0.001 (< 0.05), indicating that H₀ was rejected and H₁ was accepted. These findings demonstrate that the implementation of the Outdoor Learning model has a significant positive effect on improving the fundamental motor skills of first-grade students. Therefore, the Outdoor Learning model can serve as an effective alternative instructional approach in Physical Education to enhance fundamental motor skills among elementary school students.